Dengue serology–role of NS1 antigen: evaluation and future prospect - Surinder Kumar; Raminder Sandhu; Pallavi Sayal; Shalley Dahiya; Diksha Budhani (International Journal of Medical Research and Review, 2016)
Introduction: According to the estimates, nearly 70% of the disease burden occurs in Asia and is on constant rise. Dengue virus infection has emerged as a major public health concern across the globe in terms of mortality, morbidity and public health cost.Aims & Objectives: This study was undertaken to evaluate the significance of NS1 Ag detection in dengue IgM negative sera as marker for early detection and to compare the rapid detection test kits (RDT’s) with Enzyme linked immunosorbent assay (ELISA).Material & Method: A total of 5283 samples from, were screened for dengue serology by Immunochromatography based lateral flow assay for presence of IgM and IgG anti Dengue antibody and NS 1 Ag. Results of 169 samples were further confirmed using ELISA technique for NS1 Ag in an attempt to compare RDT’s with ELISA.Results: Out of 5283 samples screened, 146/5283 (2.76%) tested positive for dengue antibody, out of which 85/146(58.21%) were positive for DEN Ig M and 61/146(41.78%) showed presence of both IgG and IgM. Out of 5137 seronegative samples, 1930(37.57%) were positive for DEN NS1 Ag. Overall, sensitivity of RDT was 100.00%, specificity-90.16%, PPV- 94.73%, NPV-100.00 % and Efficiency of test -96.44%.Conclusion: NS1 Ag assay holds promise as useful tool in early diagnosis for detecting dengue infection during acute phase of infection when IgM antibodies are not formed to the detectable levels. Also, accurate and affordable diagnostic tests are a crucial component of combating this debilitating mosquito-borne infection.